2014
DOI: 10.1080/13811118.2013.826156
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Dialectical Behavior Therapy with Suicidal and Self-Harming Adolescents with Multi-Problems: Training, Adherence, and Retention

Abstract: We evaluated the feasibility of DBT training, adherence, and retention preparing for a randomized controlled trial of Dialectical Behavior Therapy (DBT) adapted for Norwegian adolescents engaging in self-harming behavior and diagnosed with features of borderline personality disorder. Therapists were intensively trained and evaluated for adherence. Adherence scores, treatment retention, and present and previous self-harm were assessed. Twenty-seven patients were included (mean age 15.7 years), all of them with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 34 publications
2
19
0
2
Order By: Relevance
“…This trend was observed in four of the reviewed studies (Fleischhaker et al, 2011; Mehlum et al, 2014; Rathus & Miller, 2002; Tørmoen et al, 2014). The two additional studies (James et al, 2014; Woodberry & Popenoe, 2008) noted that subjects demonstrated symptoms consistent with BPD (i.e.…”
Section: Diagnostic Inclusion Criteriamentioning
confidence: 52%
See 2 more Smart Citations
“…This trend was observed in four of the reviewed studies (Fleischhaker et al, 2011; Mehlum et al, 2014; Rathus & Miller, 2002; Tørmoen et al, 2014). The two additional studies (James et al, 2014; Woodberry & Popenoe, 2008) noted that subjects demonstrated symptoms consistent with BPD (i.e.…”
Section: Diagnostic Inclusion Criteriamentioning
confidence: 52%
“…Four studies utilized a non-control group preand post-test comparison design; two included extended post-treatment follow-up (Fleischhaker et al, 2011; James et al, 2014; Tørmoen et al, 2014; Woodberry & Popenoe, 2008) and two studies included a comparison group (Mehlum et al, 2014; Rathus & Miller, 2002). Mehlum et al (2014) was the only randomized control trial study utilizing a usual care as the control condition.…”
Section: Review Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In den letzten Jahren wurden Adhärenz und therapeutische Allianz als wichtig für einen guten Therapieerfolg beschrieben [Priebe et al, 2012;Tormoen et al, 2014]. Zu diskutieren ist, ob sich in unserer Risikogruppe, charakterisiert durch hohe «Dysphorie», die therapeutische Allianz gegebenenfalls vermindert hat und damit Therapieerfolge möglicherweise reduziert wurden.…”
Section: Diskussionunclassified
“…The most often referred treatments are Mentalization Based Treatment for Adolescents (MBT-A) (Laurenssen et al, 2014;Rossouw, 2013;Rossouw & Fonagy, 2012) and Dialectical Behavior Therapy for Adolescents (DBT-A) (Fleischhaker et al, 2011;Katz, Cox, Gunasekara, & Miller, 2004;MacPherson, Cheavens, & Fristad, 2013;McDonell et al, 2010;Miller, Rathus, & Linehan, 2007;Rathus & Miller, 2002;TØrmoen et al, 2014). However, these methods are extensive, not always feasible in clinical practice and treat NSSI in a BPD context.…”
Section: Specific Psychological Treatmentmentioning
confidence: 99%